Problems in The Implementation of The Mubasyarah Method in Teaching Maharat Al-Kalam in The Takhoshus Class of MA Al Firdaus Wangen Klaten - Akhmad Sholahuddin (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
Speaking skills, also known as maharah al-kalam, are among the most emphasized skills in language learning. In this skill, students are required to actively communicate in Arabic, both with their peers and with the teacher. One of the methods used in this learning process is the mubasyarah method, which is an Arabic teaching approach through direct communication using the target language. However, in practice, many challenges or problems are often encountered. This study aims to analyze the problems that arise in the implementation of the mubasyarah method in teaching maharah al-kalam to takhoshus class students at MA Al Firdaus Wangen Klaten. The research employed a descriptive qualitative method with observation, interview, and documentation techniques. The findings revealed several problems, including students’ limited vocabulary, lack of confidence in speaking, insufficient learning media, ineffective time management, and the dominance of the mother tongue in the classroom. The study concludes that the effectiveness of the mubasyarah method in improving maharah al-kalam is often hindered by these challenges. Addressing them requires supportive strategies such as more intensive vocabulary habituation, encouraging students to practice speaking Arabic in various contexts, maximizing the use of learning media, and providing regular motivation. It is therefore expected that the mubasyarah method can become a truly effective approach to enhancing students’ speaking skills in Arabic.